Development of chromosome segment substitution lines harboring Oryza nivara genomic segments in Koshihikari and evaluation of yield-related traits - Furuta, Tomoyuki (Breed Sci, 2016)
Chromosome segment substitution lines (CSSLs) are rich genetic resources that can be mined for novel, agriculturally useful loci or that can be used directly as materials for breeding. To date, a number of rice CSSLs have been developed by crossing rice cultivars with its wild relatives as a means to tap into the potential of wild alleles in rice improvement. Oryza nivara is a wild relative of rice that is thought to be a progenitor of O. sativa spp. indica. In the present study, 26 CSSLs that covers the entire genome of O. nivara as contiguous, overlapping segments in the genomic background of a japonica cultivar, O. sativa cv. Koshihikari were developed. Evaluation of the CSSLs for several agriculturally important traits identified candidate chromosome segments that harbors QTLs associated with yield and yield-related traits. The results of the study revealed the potential of O. nivara as a source of novel alleles that can be used to improve the existing japonica cultivar.